2014
DOI: 10.1016/j.jgeb.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Indirect organogenesis from various explants of Hildegardia populifolia (Roxb.) Schott & Endl. – A threatened tree species from Eastern Ghats of Tamil Nadu, India

Abstract: Hildegardia species are an important resource for fiber industry. This investigation was conducted to develop a plant regeneration protocol for Hildegardia populifolia (Roxb.) Schott & Endl. via indirect organogenesis Callus was obtained from leaf, internode and petiole explants, among these explants internode explant gave best result on MS medium supplemented with different concentrations of 2,4-Dichlorophenoxy acetic acid (2,4-D). The highest percentage (100%) of regeneration was obtained with benzyladenine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…In the other study, Parasharami et al [27] demonstrated that MS medium supplemented with 2.4 mg/l 2,4-D plus 1.0 mg/l BAP had the highest callus formation from fruit segments of F. religiosa. Ultimately, the difference results that obtained from those studies maybe due to the age, source, and the internal PGRs of explants [2], [22]. The calli that obtained from various concentrations of auxins and cytokinins possessed a friable type with yellow-brownish color (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In the other study, Parasharami et al [27] demonstrated that MS medium supplemented with 2.4 mg/l 2,4-D plus 1.0 mg/l BAP had the highest callus formation from fruit segments of F. religiosa. Ultimately, the difference results that obtained from those studies maybe due to the age, source, and the internal PGRs of explants [2], [22]. The calli that obtained from various concentrations of auxins and cytokinins possessed a friable type with yellow-brownish color (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the conservation of plant biodiversity is indispensable for future crops safety due to increasing challenges of biotic and abiotic stresses ( Alexandratos and Bruinsma, 2012 ; Gupta et al., 2016 ). In this regard, in vitro techniques permit improvement in various traits associated with plant growth and yield that can, later, be used for ex-situ conservation ( Lavanya et al., 2014 ). The active plant compounds obtained from rare or endangered species can be manufactured by in vitro techniques without adverse environmental effects and in agreement with the bio- sustainability matters that the market demands ( Figures 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bark of the stem and leaves are also used as an antidote to dog bites and to curing malaria in the traditional medical practice of Tamil Nadu and Andhra Pradesh Varaprasad et al 2009). Lavanya et al (2012) reported that different parts of the tree are used in various ayurvedic commercial preparations. Therefore, the different uses of H. populifolia locally and commercially have contributed to its current status.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds located in the litter rich areas of rock crevices/openings germinate and produce seedlings immediately during the rainy season and hence, they are non-dormant. Lavanya et al (2012) stated that the seeds of H. populifolia are viable for a few months suggesting that they may germinate in the next rainy season. These authors also noted that the seed mode is the main propagation method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation